Hubungan Persepsi Label Visual Kemasan Rokok Dan Fatwa Haram Merokok Dengan Perilaku Merokok Siswa SMP Muhammadiyah 7 Surakarta - Zakiyah, Arnindya Khalimatu; , Yuli Kusumawati, S.KM, M.Kes (Epid); , Kusuma Estu Werdani, SKM., M.Kes (2016)
Smoking behavior in adolescents will destroy the young generation in the future. The highest smoking student from preliminary survey was at junior high school of Muhammadiyah 7 Surakarta there was equal to 50%.This research aims to determine the relationship of perception visual label in cigarette packing and illicit cigarettes fatwa with student smoking behaviour. Determination of reaserach sites by the highest average of students smoke at junior high school of Muhammadiyah 7 Surakarta. This research was an observational study with cross sectional design. Population this research was 85 students with male gender. The sample as much as 76 students used simple random sampling methods as the sampling technique. Chi-square statistic test were used as bivariate analysis, with significance α=0.05 (Confidence level 95%). The results of research showed that there were no relationship between knowledge of visual label in cigarette packing and illicit cigarettes fatwa (p=0,050), the perception of visual label in cigarette packing (p=1,000), the attitude of illicit cigarettes fatwa (p=1,000) with smoking behavior of student. Key Words: Smoking behaviour, knowledge, perception, attitude, visual label in cigarette packing, and illicit cigarettes fatwa.